AB1095 DIAGNOSTIC PERFORMANCE OF THE AORTIC WALL THICKENING DETERMINED BY ROUTINE CT-SCAN FOR THE DIAGNOSIS OF AORTITIS OVER 50 YEARS OF AGE. (2nd June 2020) - Grouteau, G.; Lafourcade, F.; Fayolle, H.; Ricard, C.; Balardy, L.; Delobel, P.; Constantin, A.; Beyne Rauzy, O.; Alric, L.; Payoux, P.; Hitzel, A.; Faruch, M.; et al.
Abstract : Background: Making the diagnosis of aortitis may be challenging in the "real life". 18 F-FDG PET/CT (PET) has emerged has the gold standard to diagnose aortitis but it is expensive and not always quickly available. Injected CT-scan (CT) can also be used to diagnose aortitis, which is suspected when there is an extended circumferential, non-atherosclerotic increase of the aortic wall thickness (AWT). However, data are lacking on the diagnostic performances of AWT to diagnose aortitis. Objectives: To describe the diagnostic performance of AWT measured by CT to diagnose aortitis in patients over 50 years of age. Methods: We performed a monocentric retrospective study between 2013 and 2018 including 1) all patients over 50 years of age who had performed a PET for inflammation or fever of unknown origin or for suspicion of classical giant cell arteritis (GCA), aortitis or large vessel vasculitis (LVV); 2) with an injected CT-scan performed in the 30 days before or after PET; 3) not diagnosed to have cancer or infection 4) exposed to corticosteroids for less than 3 days at the time of CT and PET. The gold standard for aortitis was PET positivity according to the 2018 European consensus grading criteria (1). AWT was measured at different aortic segments (ascending aorta, descending thoracic aorta and suprarenal abdominal aorta) by a single radiologist unaware of the result of PET and of the previous interpretation of CT-scan. Results: Eighty-nine patients were included (female: 47%; mean age 68.8 (50-93) years; GCA: n=28). Twenty patients had aortitis according to the PET result (GCA: n=16). Mean maximal aortic wall thickening was: 3.25 mm (median: 3.3; range: 2-4.6) in the aortitis group and 2.2 mm (median: 2.1; range 1-3.8) in the negative PET group (p < 0.001). The best ROC curve AUC (85%) was obtained considering the maximal AWT on the thoracic and suprarenal abdominal aorta only. The AUC of the ROC curve at the ascendant thoracic aorta was poor (75%) (Figure). The Youden's index of the ROC curve was 2.6 mm with a sensitivity of 85 % and specificity of 71 % (Table) for aortitis diagnosis. An AWT ≤ 2.0 mm exclude the diagnosis of aortitis. The 3 mm threshold had a PPV of only 52% and an AWT ≥ 4 mm was fully specific. Conclusion: Aortitis diagnosis using a routine injected CT-scan interpreted by a single radiologist may be certain when showing an AWT ≥ 4 and excluded for an AWT≤ 2.0. The threshold of 3 mm seems not sufficiently specific to diagnose aortitis without a confirmatory PET. References: [1]Riemer H.J.A. Slart et al. FDG-PET/CT(A) imaging in large vessel vasculitis and polymyalgia rheumatica: joint procedural recommendation of the EANM, SNMMI, and the PET Interest Group (PIG), and endorsed by the ASNC. Eur J Nucl Med Mol Imaging. 2018 Jul;45(7):1250–69. Disclosure of Interests: None declared